The Struggle of the Aceh Society in the Historical Framework of Malay and Nusantara - Zulhelmi, Anshar; Fajri, Akmal; AR, Nurdin; Hisyam, Rasyad; Trisnady, Ivan Aulia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study describes the attitude of the struggle of the people of Ash from the historical point of view as well as the form of the contribution of the fighting of Ash to Nusantara and the culture of Ash. This qualitative research data is collected by means of the study of the library by collecting the reading materials that correspond to the discussion. The data is then done reading techniques and recorded from the reading results of the materials related to the struggle of aceh and contribution to nusantara and culture. The results of reading and recording techniques, will answer the form of the problem is how to fight aceh against nusantara, and how the fight of Aceh in culture. Thus it can be concluded that the aceh's historical championship is very great against Nusantara and culture also from the point of view of Islamization in Nusantara. It is based on the territory of the Acheh and the attitude of the acheh monarchy as well as the diplomatic relations carried out by the Aceh kingdoms. ————————————————————————————————Kajian ini mendeskripsikan tentang sikap perjuangan masyarakat Aceh ditinjau dari sejarah serta bentuk kontribusi perjuangan masyarakat Aceh terhadap Nusantara dan kebudayaan Aceh. Data penelitian kualitatif ini dikumpulkan dengan cara studi kepustakaan dengan mengumpulkan bahan-bahan bacaan yang sesuai dengan pembahasan. Data tersebut kemudian dilakukan teknik membaca dan dicatat dari hasil pembacaan materi-materi yang berkaitan dengan perjuangan aceh dan kontribusinya terhadap nusantara dan kebudayaan. Hasil dari teknik baca dan rekam, akan menjawab berupa permasalahan bagaimana perjuangan aceh melawan nusantara, dan bagaimana perjuangan aceh secara budaya. Dengan demikian dapat disimpulkan bahwa keutamaan sejarah aceh sangat besar terhadap nusantara dan budaya juga dari sudut pandang islamisasi di nusantara. Hal ini didasarkan pada wilayah Aceh dan sikap monarki Aceh serta hubungan diplomasi yang dilakukan kerajaan-kerajaan Aceh.